ANALISIS PERAN RITUS CEAR CUMPE DALAM MENANAMKAN NILAI-NILAI MORAL PADA MASYARAKAT MANGGARAI - Sebastianus Mardi; Andri Fransiskus Gultom; Romadhon (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2026)
This study aims to analyze the role of the Cear Cumpe ritual in instilling moral values in Manggarai society, identify the gap between traditional values and social practices, and examine the relevance of the ritual as a medium for character education based on local culture. The research employed a descriptive qualitative approach using observation, in-depth interviews, and documentation as data collection techniques. The informants consisted of traditional leaders, community leaders, religious leaders, youth leaders, educators, parents, and village government representatives in Bea Ngencung Village, East Manggarai Regency. The findings reveal that the Cear Cumpe ritual contains moral values such as social solidarity, collective responsibility, togetherness, respect for ancestors, and mutual cooperation. These values are transmitted through active community participation in every stage of the ritual process. However, the study also found a gap between the moral values embedded in the ritual and the social behavior of the community, especially among younger generations who show declining participation and understanding of traditional customs due to modernization, technological development, and changing lifestyles. Nevertheless, the Cear Cumpe ritual remains relevant as a contextual medium for revitalizing character education because it provides direct value-learning experiences through socio-cultural practices within the community.